Multimorbidity patterns and health-related quality of life in Jamaican adults: a cross sectional study exploring potential pathways - Craig, Leslie S.; Cunningham-Myrie, Colette A.; Theall, Katherine P.; Gustat, Jeanette; Hernandez, Julie H.; Hotchkiss, David R. (Frontiers in Medicine, 2023)
Introduction: Multimorbidity and health-related quality of life (HRQoL) are intimately linked. Multiple chronic conditions may adversely affect physical and mental functioning, while poorer HRQoL may contribute to the worsening course of diseases. Understanding mechanisms through which specific combinations of diseases affect HRQoL outcomes can facilitate identification of factors which are amenable to intervention. Jamaica, a middle-income country with high multimorbidity prevalence, has a health service delivery system dominated by public sector provision via a broad healthcare network. This study aims to examine whether multimorbidity classes differentially impact physical and mental dimensions of HRQoL in Jamaicans and quantify indirect effects on the multimorbidity-HRQoL relationship that are mediated by health system factors pertaining to financial healthcare access and service use. Materials and methods: Latent class analysis (LCA) was used to estimate associations between multimorbidity classes and HRQoL outcomes, using latest available data from the nationally representative Jamaica Health and Lifestyle Survey 2007/2008 (N=2,551). Multimorbidity measurement was based on self-reported presence/absence of 11 non-communicable diseases (NCDs). HRQoL was measured using the 12-item short-form (SF-12) Health Survey. Mediation analyses guided by the counterfactual approach explored indirect effects of insurance coverage and service use on the multimorbidity-HRQoL relationship. Results: LCA revealed four profiles, including a Relatively Healthy class (52.7%) characterized by little to no morbidity and three multimorbidity classes characterized by specific patterns of NCDs and labelled Metabolic (30.9%), Vascular-Inflammatory (12.2%), and Respiratory (4.2%). Compared to the Relatively Healthy class, Vascular-Inflammatory class membership was associated with lower physical functioning (β=-5.5; p<0.001); membership in Vascular-Inflammatory (β=-1.7; p<0.05) and Respiratory (β=-2.5; p<0.05) classes was associated with lower mental functioning. Significant mediated effects of health service use, on mental functioning, were observed for Vascular-Inflammatory (p<0.05) and Respiratory (p<0.05) classes. Conclusions: Specific combinations of diseases differentially impacted HRQoL outcomes in Jamaicans, demonstrating the clinical and epidemiological value of multimorbidity classes for this population, and providing insights that may also be relevant to other settings. To better tailor interventions to support multimorbidity management, additional research is needed to elaborate personal experiences with healthcare and examine how health system factors reinforce or mitigate positive health-seeking behaviours, including timely use of services.